Fluency aspects of oral narrative task in del22q11.2 syndrome - Santos, Amanda Oliveira [UNESP]; Rossi, Natalia Freitas [UNESP]; Tandel, Maria da Conceição Faria Freitas [UNESP]; Richieri-Costa, Antonio; Giacheti, Célia Maria [UNESP] (FapUNIFESP (SciELO), 2016)
Purpose: To investigate the fluency aspects of the oral narrative task in individuals with del22q11.2 syndrome and compare them with those of individuals with typical language development. Methods: Fifteen individuals diagnosed with del22q11.2 syndrome, both genders, aged 7-17 years participated in this study. They were compared with 15 individuals with typical language development, with similar gender and chronological age profiles. The oral narrative was elicited using the book Frog, Where Are You?, and the fluency aspects were analyzed according to speech rate and type and frequency of disfluency (typical and stuttering). The number and duration of pauses were also investigated. The data were statistically analyzed. Results: The group with del22q11.2 syndrome showed a higher average when compared with the group without the syndrome for the percentage of typical disfluencies, mainly hesitation and revision. The group presenting the syndrome also showed a higher average for stuttering disfluencies, with pause as the most frequent disfluency. With respect to speech rate, the group with the syndrome presented a lower average for the number of words and syllables per minute. Individuals with del22q11.2 syndrome showed greater difficulties of narration than their peers. Conclusion: The fluency aspects of the oral narrative task in subjects with del22q11.2 syndrome were similar to those of individuals with typical language development regarding the presence of hesitation, revision, and pause, but they were different with respect to frequency of disfluency, which was higher in individuals with the syndrome.
Keywords: DiGeorge Syndrome; Language; Narration; Speech; Speech Production Measurement